2015
DOI: 10.1111/jace.13656
|View full text |Cite
|
Sign up to set email alerts
|

Color Variation Between PSL and PL in CaAl2Si2O8:Tb3+ with the Assistance of Trap Level

Abstract: We reported a green photoluminescence (PL) emission associated with a blue photo-stimulated luminescence (PSL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1b) demonstrate that Tb 2 O 3 would have made only a minor contribution to the green luminescence from m-CAS-Tb-Edge. Additionally, although anorthite is a mother material for Tb 3+ -containing phosphors, 31,32 the relatively weak reection attributed to anorthite (Fig. 3f) indicates that the green luminescence from m-CAS-Tb-Edge was due to the formation of Tb 3+ -doped metastable CaAl 2 Si 2 O 8.…”
Section: Resultsmentioning
confidence: 99%
“…1b) demonstrate that Tb 2 O 3 would have made only a minor contribution to the green luminescence from m-CAS-Tb-Edge. Additionally, although anorthite is a mother material for Tb 3+ -containing phosphors, 31,32 the relatively weak reection attributed to anorthite (Fig. 3f) indicates that the green luminescence from m-CAS-Tb-Edge was due to the formation of Tb 3+ -doped metastable CaAl 2 Si 2 O 8.…”
Section: Resultsmentioning
confidence: 99%
“…4(b) and (c) ; this also indirectly supports the occurrence of ET among Ce 3+ , Eu 2+ and Eu 3+ . 30 Meanwhile, with increasing x , the emission band of Eu 2+ still shows a slight red shift, which is probably due to two reasons: the change in the crystal field environment and the selective excitation of Eu 2+ at the different sites. In addition, as the Eu content increases, the distance between the sensitizer Ce 3+ and the activators Eu 2+ and Eu 3+ becomes shorter.…”
Section: Resultsmentioning
confidence: 97%
“…According to our previous work, it was found that the blue emission of Tb 3+ dominant observed when suitable defects levels were introduced. [8] Therefore, with a view to practical applications, it would be very meaningful to prepare and design the novel white-blue LPPs of CGO:Tb 3+ . The unique PET from CGO to Tb 3+ would generate some exciting phenomena that have never been reported before.…”
Section: Introductionmentioning
confidence: 99%